What Grades and Achievement Tests Measure - Lex Borghans; Bart H.H. Golsteyn; James J. Heckman; John Eric Humphries (Institute for the Study of Labor (IZA), 2016)
Intelligence quotient (IQ), grades, and scores on achievement tests are widely used as measures of cognition, yet the correlations among them are far from perfect. This paper uses a variety of data sets to show that personality and IQ predict grades and scores on achievement tests. Personality is relatively more important in predicting grades than scores on achievement tests. IQ is relatively more important in predicting scores on achievement tests. Personality is generally more predictive than IQ of a variety of important life outcomes. Both grades and achievement tests are substantially better predictors of important life outcomes than IQ. The reason is that both capture personality traits that have independent predictive power beyond that of IQ.
Keywords: J24; D03; 330; IQ; achievement tests; grades; personality traits